PENGEMBANGAN MEDIA AUDIO VISUAL MACROMEDIA FLASH 8 PADA MATERI PEREDARAN DARAH DI KELAS V - Riska Rahmadini; Sisri Wahyuni (LP2M Universitas Adzkia, 2025)
This research was motivated by the limited use of projectors in learning activities, teachers’ low competence in using computer-based media, and students’ difficulties in understanding abstract science material because learning was delivered verbally. The study aimed to determine the development, validity, practicality, and effectiveness of audio-visual media using Macromedia Flash 8 in science learning on the topic of the circulatory system for fifth-grade elementary students. This study employed a Research and Development (R&D) method using the 4-D model, consisting of define, design, development, and dissemination stages. The trial was conducted with 10 fifth-grade students. The results showed that the developed media achieved an average validity score of 91.94% categorized as very valid, practicality scores of 95.8% from teachers and 89.99% from students categorized as very practical, and an effectiveness score of 86.00% categorized as very effective. Therefore, the developed media is feasible for use in elementary science learning.